KAJIAN PREFERENSI PEMILIHAN MODA PENGUMPAN KOMUTER KRL STASIUN BEKASI, KOTA BEKASI - Reny Savitri; Herti Lasita (Jurnal Ilmiah Plano Krisna, 2024)
Several intercity feeder modes are available. However, factors that can explain the commuters' choices is still unknown. Therefore, this study examines factors related to their preferences in choosing intercity feeders. It focuses on data from passengers of electric rail cars (or Kereta Rel Listrik – KRL in Indonesia) who had to choose between public transport and an online motorcycle taxi when traveling to Bekasi Station in Bekasi City. The research covers five factors associated with their selection preferences:, public transport safety, public transport comfort, public transport regularity and public transport travel costs.The data analysis uses descriptive statistics, hypothesis testing and overlay. The results show that commuters' preference are highly influenced by public transport regularity, public transport travel costs, and online motorcycle taxi travel costs, whereas the travel cost factor of online motorcycle taxis being the largest. The research findings can provide input for the Bekasi City Spatial Plan.